2021
DOI: 10.1007/s11239-021-02401-x
|View full text |Cite
|
Sign up to set email alerts
|

Clinical outcome with different doses of low-molecular-weight heparin in patients hospitalized for COVID-19

Abstract: A pro-thrombotic milieu and a higher risk of thrombotic events were observed in patients with CoronaVirus disease-19 (COVID-19). Accordingly, recent data suggested a beneficial role of low molecular weight heparin (LMWH), but the optimal dosage of this treatment is unknown. We evaluated the association between prophylactic vs. intermediate-to-fully anticoagulant doses of enoxaparin and in-hospital adverse events in patients with COVID-19. We retrospectively included 436 consecutive patients admitted in three I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(23 citation statements)
references
References 35 publications
0
19
0
2
Order By: Relevance
“…[42,43] Intravascular coagulation and microthrombi formation Lead to increased wasted ventilation and less efficient carbon dioxide removal. [44][45][46][47][48][49][50][51][52][53][54][55][56][57][58][59][60][61][62] Diffuse alveolar damage (DAD) Lead to hypoxia at the edematous alveoli.…”
Section: Pathogenic Mechanismsmentioning
confidence: 99%
See 3 more Smart Citations
“…[42,43] Intravascular coagulation and microthrombi formation Lead to increased wasted ventilation and less efficient carbon dioxide removal. [44][45][46][47][48][49][50][51][52][53][54][55][56][57][58][59][60][61][62] Diffuse alveolar damage (DAD) Lead to hypoxia at the edematous alveoli.…”
Section: Pathogenic Mechanismsmentioning
confidence: 99%
“…Aspirin administration had an association with less mechanical ventilation and reduced ICU cases, but showed no apparent association with the fatality rate (Table 2) [51]. The therapeutic effects of low molecular weight heparin have also been investigated comprehensively [52][53][54][55][56][57][58]. Heparin may reduce the risk of in-hospital mortality and decrease the occurrence of severe cases.…”
Section: Ventilation-perfusion Mismatch and Intravascular Coagulation In Covid-19mentioning
confidence: 99%
See 2 more Smart Citations
“…Mesas et al identi ed Interleucin 6 (IL-6) together with preexisting diseases as predictors of a lethal course in patients under the age of 60 and elevated bilirubin and liver enzymes together with decreased albumin in patients older than 60 years (12). Mennuni et al found that the dosage of low molecular weight heparin hardly affected outcome (13).…”
Section: Introductionmentioning
confidence: 99%